Graphene-polymer nanocomposites for thermal conductive applications. Issue 1 (February 2020) - Zhang, X; Zheng, J; Du, Y Q; Wang, Z W; Wu, Y D; Luo, G
Abstract: Graphene has been widely used in improving the physical properties of polymer composites. By adding different forms of graphene nanomaterials to the polymer matrix, the thermal conductivity of the polymer composite can be effectively improved. In this work, the research of graphene-polymer thermal composites is reviewed, and the main preparation methods and material design principles of graphene-polymer composites are analysed. The main preparation methods include improving the dispersion, surface modification, tailoring the size and loading, applying synergistic effect and building three-dimensional network of graphene.